Conditional Release of Privates According to Law Number 22 of 2022 Concerning Correction - Fitrah Mulya Al Faris; Dahris Siregar; Muhammad Farhan Septian; Lucky Billy Boy; Muhammad Akbar Wibowo; Andrean Harahap; Adinda Dwi Cahya; Silvi Aulia Putri; Zarahtul Janna (Inovasi Pratama Internasional. Ltd, 2023)
This article discusses the terms and procedures for parole of convicts according to law number 22 of 2022 concerning correctional facilities. Analysis was carried out on regulations related to parole including Regulations of the Minister of Law and Human Rights and laws related to parole. This research was conducted based on qualitative methods using literature studies sourced from laws and regulations, books and scientific journal articles. This article concludes that conditional release of convicts complies with applicable operational standards.